STRIVING TO GET LOVE REFLECTED IN SUSANNA WHITE'S JANE EYRE TELEVISION MINISERIES (2006): AN INDIVIDUAL PSYCHOLOGICAL APPROACH - WINDIASTUTI , NURLITA (2011)
This study investigates" How striving to get love is reflected in Susanna White‟s Jane Eyre Television Miniseries?" viewed from individual psychological approach. Therefore, this research is aimed at analyzing the structural elements of the Jane Eyre Television Miniseries and describing striving to get love of Jane Eyre in the story based on individual psychological approach. This research paper is qualitative research. The object of the study is Jane Eyre Television Miniseries directed by Susanna White. The primary data source is Jane Eyre television Miniseries itself and the secondary data sources are the other sources related to the movie. The method of data collection is documentation research. The technique of data analysis is descriptive analysis. Based on the analysis, there are two conclusions. First, from the structural analysis it shows that each of the element is interrelated to each other and forms unity. Second, from the individual psychological analysis, it shows that if someone wants to get love for someone, she must fight for her love although she confronts many obstacles in her struggle.